PENGARUH TERAPI PIJAT KAKI TERHADAP STATUS HEMODINAMIK PADA PASIEN TERPASANG VENTILATOR DI INTENSIVE CARE UNIT (ICU) RSUD ULIN BANJARMASIN - Izma Daud; Revina Nurul Sari (Journal of Nursing Invention, 2020)
Background: Hemodynamic instability of patients admitted to the intensive care unit (ICU). It is caused by stressors that come from physiological, psychological, and environmental aspects. The therapy provided for patients in the ICU is dominated by pharmacological therapy. While based on holistic nursing theory, care for patients can be optimized with complementary therapies such as foot massage.Objective: to determine the effect of foot massage therapy on hemodynamic status in patients attached to ventilators.Methods: Research design using pre-experiment with one group pre-post test design method. The research sample amounted to 31 respondents using purposive sampling technique. The research was analyzed using the Wilcoxon test.Results: there is a significant effect of foot massage on reducing systolic blood pressure 0.020 (<0.05), diastolic blood pressure 0.025 (<0.05), MAP 0.013 (<0.05), pulse 0.034 (<0.05), respiration 0.001 (<0.05) but there is no significant effect of foot massage on increasing oxygen saturation 0.317 (>0.05).Conclusion: Foot massage can improve blood circulation, pressure on the muscles can gradually relax the tension so as to help facilitate blood flow to the heart.